Oxidative Stress Linked Organ Lipid Hydroperoxidation and Dysregulation in Mouse Model of Nonalcoholic Steatohepatitis: Revealed by Lipidomic Profiling of Liver and Kidney - Yue Wu; Zhen Chen; Hirotoshi Fuda; Takayuki Tsukui; Xunzhi Wu; Nianqiu Shen; Natsuki Saito; Hitoshi Chiba; Shu-Ping Hui (MDPI AG, 2021)
Nonalcoholic steatohepatitis (NASH) is a prevalent disease related to lipid metabolism disorder and oxidative stress. Lipid hydroperoxidation is known to be a critical driving force of various disorders and diseases. However, the combination of both intact and hydroperoxidized lipids in NASH has not yet been studied. In this work, the liver and kidney samples from NASH-model mice were comprehensively investigated by using the LC/MS-based lipidomic analysis. As a result, triglycerides showed the amount accumulation and the profile alteration for the intact lipids in the NASH group, while phosphatidylethanolamines, lysophosphatidylethanolamines, plasmalogens, and cardiolipins largely depleted, suggesting biomembrane damage and mitochondria dysfunction. Notably, the lipid hydroperoxide species of triglyceride and phosphatidylcholine exhibited a significant elevation in both the liver and the kidney of the NASH group and showed considerable diagnostic ability. Furthermore, the relationship was revealed between the lipid metabolism disturbance and the lipid hydroperoxide accumulation, which played a key role in the vicious circle of NASH. The present study suggested that the omics approach to the lipid hydroperoxide profile might be the potential diagnostic marker of NASH and other oxidative stress-related diseases, as well as the evaluative treatment index of antioxidants.